THE PRODUCT CHARACTERISTICS OF TREATED-FERRONICKEL SLAG PRODUCED BY ALKALI FUSION AND CARBOTHERMIC PROCESS - Reza Miftahul Ulum (National Research and Innovation Agency (BRIN), 2021)
The utilization of slag as a secondary resource is usually processed by a reduction process with coal reducing agents or by leaching process. However, this study will use palm kernel shell as an alternative reducing agent to substitute coal. Palm kernel shell was chosen as an alternative reducing agent because of their availability in Indonesia. The purpose of this study is to determine the effect of palm kernel shell as reducing agent and its concentration (wt.%) to the ferronickel slag reduction process. The initial sample is ferronickel slag which had been proceed by alkali fusion by adding 20 wt.% sodium carbonate (Na2CO3) as an additive and then roasted. The roasted product is then mixed with palm kernel shell reductant by ratio (sample : reductant), which are 15:85, 20:80, and 25:75 in weight percent. Samples that have been mixed are then compacted using compacting machine. Then the reduction process is carried out using a tube furnace at a temperature of 1100°C for 60 minutes with a heating rate of 10°C/minute. The palm kernel shells were analyzed using ultimate and proximate analysis, while the reduced product is then characterized by SEM-EDS and XRD for further analysis. Based on the results of the characterization, in this study it was found that the reduction process using palm kernel shell produces products in the form of iron metal, magnetite, hematite, and sodium silicate. The optimum reducing agent concentration in this study is by adding 15 wt.% reductant.